Post-traumatic stress disorder (PTSD) and associated depressive symptoms among residents of the regions heavily affected by the Russian aggression - Napryeyenko, Олександр; Dolynskyi, Роман (Psychosomatic Medicine and General Practice, 2024)
Abstract Post-traumatic stress disorder (PTSD) is a chronic mental disorder that leads to a decrease in the quality of life and an increase in the economic burden. Exposure to traumatic stress is the main trigger for the development of PTSD. PTSD is a significant challenge for mental health both during and after wars.. PTSD prevalence among residents of the de-occupied and heavily war-affected communities of Chernihiv, Kharkiv, Dnipro and Sumy oblast was analyzed; the risk of concomitant depression symptoms was assessed. PTSD average prevalence among the regions heavily affected by the Russian aggression was 27.4%. Young people at the age of 18-29 appeared the most susceptible to PTSD and demonstrated a prevalence of PTSD signs of 32.6%. Detected PTSD in the vast majority of cases was accompanied by the signs of depression. Clinical PTSD signs increased the risk of depression disorders 15 times. Keywords: post-traumatic stress disorder (PTSD), screening, full-scale invasion, depressive symptoms, depressive disorders, civilian population, psychotraumatic factors, full-scale russian aggression, prolonged war, comorbidity, diagnostic questionnaires.